Spatial and Temporal Variation of the Blowflies Community (Diptera: Calliphoridae) From an Urban Area in Northern South America (2018)
Blowflies (Diptera: Calliphoridae) are necrophagous flies with ecological, medical, veterinary, and forensic importance. These flies carry pathogens that they spread to animals and humans, and produce myiasis. Furthermore, they are useful tools in forensic science as indicators of postmortem intervals, and in biomedicine they are successfully used in larval therapy. This study aimed to assess the spatiotemporal variation of the blowflies community from the urban area of Sincelejo City, located in the Colombian Caribbean region. Samplings were conducted from May 2012 to April 2013, using Van Someren Rydon-traps baited with bovine meat, fish, and chicken that decomposed for 48 h. Six species were registered, Cochliomyia macellaria (Fabricius, 1775) was the most abundant, followed by Lucilia eximia (Wiedemann, 1819) and Chrysomya albiceps (Wiedemann, 1819), while Chloroprocta idioidea (RobineauDesvoidy, 1830), Chrysomya megacephala (Fabricius, 1794), and Lucilia cuprina (Wiedemann, 1830) presented the least individuals. The blowflies community did not change significantly throughout the sampling months or between the periods of low or high rainfall, nor was it influenced by weather variables. Although the species composition was the same in all sampled localities, species abundances presented significant differences. The possible causes of this pattern are discussed herein. Sex ratios were female biased for all the recorded species, except C. idioidea. Our findings provide the first assessment of the blowflies community from the urban area of Sincelejo City. Key words: necrophagous fly, medical entomology, forensic entomology, invasive species, sex ratio